Studi Gramatikal Galatia 2:11-14: Patutkah Menegur Pemimpin Rohani? - Aseng Yulias Samongilailai (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2020)
Abstract. Rebuking a spiritual leader is hardly easy, that it seem to be disrespecting someone who had been anointed by God. That is what makes more Christians keep quiet despite knowing that their spiritual leader is mistaken. Through the grammatical analysis of Galatians 2: 11-14 the writer tried to prove the propriety of a person rebuking a spiritual leader. Through this study it could be concluded that the spiritual leader deserves to be rebuked if he/ she has deviated from the the truth of the Gospel he/she himself/ herself taught.Abstrak. Menegur seorang pemimpin rohani tidaklah mudah, di mana upaya tersebut seringkali dianggap sebagai tidak menghormati orang yang telah diurapi Tuhan. Hal itulah yang membuat lebih banyak orang Kristen diam saja meskipun mengetahui  pemimpin rohaninya berbuat salah. Melalui analisis gramatikal Galatia 2:11-14 penulis hendak membuktikan kepatutan seseorang menegur pemimpin rohaninya. Melalui kajian ini dapat disimpulkan bahwa pemimpin rohani patut untuk ditegur dengan keras apabila telah menyimpang dari kebenaran Injil yang diajarkannya sendiri.